Stretching of porous poly (l-lactide-co-ε-caprolactone) membranes regulates the differentiation of mesenchymal stem cells - Lee, Geonhui; Han, Seong-Beom; Kim, Soo Hyun; Jeong, Sangmoo; Kim, Dong-Hwee (Frontiers in Cell and Developmental Biology, 2024)
Background: Among a variety of biomaterials supporting cell growth for therapeutic applications, poly (l-lactide-co-ε-caprolactone) (PLCL) has been considered as one of the most attractive scaffolds for tissue engineering owing to its superior mechanical strength, biocompatibility, and processibility. Although extensive studies have been conducted on the relationship between the microstructure of polymeric materials and their mechanical properties, the use of the fine-tuned morphology and mechanical strength of PLCL membranes in stem cell differentiation has not yet been studied.Methods: PLCL membranes were crystallized in a combination of diverse solvent-nonsolvent mixtures, including methanol (MeOH), isopropanol (IPA), chloroform (CF), and distilled water (DW), with different solvent polarities. A PLCL membrane with high mechanical strength induced by limited pore formation was placed in a custom bioreactor mimicking the reproducible physiological microenvironment of the vascular system to promote the differentiation of mesenchymal stem cells (MSCs) into smooth muscle cells (SMCs).We developed a simple, cost-effective method for fabricating porosity-controlled PLCL membranes based on the crystallization of copolymer chains in a combination of solvents and non-solvents. We confirmed that an increase in the ratio of the non-solvent increased the chain aggregation of PLCL by slow evaporation, leading to improved mechanical properties of the PLCL membrane. Furthermore, we demonstrated that the cyclic stretching of PLCL membranes induced MSC differentiation into SMCs within 10 days of culture.The combination of solvent and non-solvent casting for PLCL solidification can be used to fabricate mechanically durable polymer membranes for use as mechanosensitive scaffolds for stem cell differentiation.